Peak blood lactate concentration and its arrival time following different track running events in under-20 male track athletes - Gupta, S.; Stanula, A.; Goswami, A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine (1) the time of arrival of peak blood lactate concentration ([BLa]peak) followed by various track events and (2) significant correlation, if any, between average velocity and [BLa]peak in these events.